THE INNER ARCHITECTONICS OF IVAN FRANKO’S NOVEL “CROSS PATHS” - Lutsak, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article shows the analyses of the inner architectonics of I. Franko’s novel “Cross paths”. It is focused on the plot compositional features of the composition and system of its key images. It is parabolic variety of historiosophical discourse of the novel encoded in its name.